Unveiling the Connection Between Video Games and Mental Health Among College Students in South India - Anantha Eashwar VM; Charulatha RJ; Hariharan S; B Krishna Prasanth; Abirami Srinivasan; Ponmalar M; Keerthana Ramesh (National Journal of Community Medicine, 2024)
Introduction: Playing Video Games without control can lead to Gaming Disorder (GD) which is also called a problematic gaming pattern or video game addiction. This study is to determine the prevalence of video game disorders and the various associated factors leading to them. Methodology: This cross-sectional study was done among 930 medical students studying MBBS in a private medical college in Chengalpattu district, Tamil Nadu. Data was collected by pre-tested semi-structured questionnaire. Gaming disorder was assessed by Internet Gaming Disorder Short Form – 9 (IGD-SF 9), depression by Patient Health Questionnaire – 9, and anxiety by Generalized Anxiety Disorder - 7 Questionnaire. Data were analysed using SPSS version 26. Results: Among the study participants, 37% were males, and 63% were females. The prevalence of Internet Gaming Disorder (IGD) was 9.7%. Greater than 2 hours of gaming per day, online game genre, having academic impact due to gaming, sleep problems, and neck pain/back pain due to gaming were found to be important predictors of gaming disorder. Conclusion: Awareness has to be created among students and stakeholders regarding gaming disorders among medical college students. Further research should be done to understand the relationship between GD and psychological problems like depression and anxiety.